AN ANALYSIS OF VALUES IN ANNA KARENINA NOVEL WITH REPRESENTATION OF ANNA KARENINA’S CHARACTER - Rahmat Fajar (English Literature Department, Adab and Humanities Faculty, 2023)
This study analyzes the values ​​contained in the novel entitled